Partisipasi Masyarakat Dalam Menerapkan Pola Hidup Sehat Melalui Program Lentera Emas - Rizki Mardotillah, Nida; Muslimah, Wanda; Dwi Irfany, Tabina; Indah Permata, Sahara; Novitasari, Nastiti (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
P2WKSS location Citulang Hamlet, Tanjungsari Village, Sadananya District, Ciamis Regency has a fundamental problem. The results of the analysis show that mothers of toddlers are not optimal in creating children's food so that children's appetite is inhibited which can eventually lead to stunting. Another problem is the number of elderly people in the area who are vulnerable to diseases, one of which is hypertension. Our efforts to solve it are through the implementation of the LENTERA EMAS program with sub-programs namely MEMAHAT HATI (Making Healthy Preparations from Chicken Liver) and BULAN BAHAGIA (Happy and Active Elderly Fitness). Community participation in the LENTERA EMAS program is shown through participation in planning to participation in taking benefits. The community is involved from the beginning to the end of the process. With the aim that the community is able to solve other problems, especially regarding a healthy lifestyle with the stages that the community has known through this program. Through the cooperation of various elements of the community, the LENTERA EMAS program can be implemented smoothly. So that the output of the program can be said to be in accordance with the predetermined success indicators.